Mutiply (2x-y)^2

1 answer

To multiply \((2x - y)^2\), you can use the formula for the square of a binomial, which states that \((a - b)^2 = a^2 - 2ab + b^2\).

Here, \(a = 2x\) and \(b = y\).

So, applying the formula:

\[ (2x - y)^2 = (2x)^2 - 2(2x)(y) + y^2 \]

Calculating each term:

  1. \((2x)^2 = 4x^2\)
  2. \(-2(2x)(y) = -4xy\)
  3. \(y^2 = y^2\)

Putting it all together, we get:

\[ (2x - y)^2 = 4x^2 - 4xy + y^2 \]

Therefore, the expanded form of \((2x - y)^2\) is

\[ \boxed{4x^2 - 4xy + y^2} \]

Similar Questions
  1. The commutative, or order, property applies to which operations?A. Add & Multiply B. Subtract & Mutiply C. Add & Subtract D.
    1. answers icon 3 answers
  2. Step 1: Find the _D. distance_of the line that connects C to D and the line that connects b to c_ once these are found we will
    1. answers icon 3 answers
    1. answers icon 7 answers
    1. answers icon 1 answer
more similar questions